Structure-guided design and synthesis of C22- and C32-modified FK520 analogs with enhanced activity against human pathogenic fungi - Patrick A. Dome; Pyeonghwa Jeong; Gibeom Nam; Hongjun Jang; Angela Rivera; Anna Floyd Averette; Eunchong Park; Tzu-Chieh Liao; Maria Ciofani; Jianli Wu; Jen-Tsan Ashley Chi; Ronald A. Venters; et al. (Proceedings of the National Academy of Sciences, 2025)
Invasive fungal infections are a leading cause of death worldwide. Translating molecular insights into clinical benefits is challenging because fungal pathogens and their hosts share similar eukaryotic physiology. Consequently, current antifungal treatments have limited efficacy, may be poorly fungicidal in the host, can exhibit toxicity, and are increasingly compromised by emerging resistance. We have established that the phosphatase calcineurin (CaN) is required for invasive fungal disease and an attractive target for antifungal drug development. CaN is a druggable target, and there is vast clinical experience with the CaN inhibitors FK506 and cyclosporin A (CsA). However, while FK506 and its natural analog FK520 exhibit antifungal activity, they are also immunosuppressive in the host and thus not fungal-selective. We leverage our pathogenic fungal CaN-FK506-FKBP12 complex X-ray structures and biophysical data to support structure-based ligand design as well as structure–activity relationship analyses of broad-spectrum FK506/FK520 derivatives with potent antifungal activity and reduced immunosuppressive activity. Here, we apply molecular docking studies to develop antifungal C22- or C32-modified FK520 derivatives with improved therapeutic index scores. Among them, the C32-modified FK520 derivative JH-FK-44 ( 7 ) demonstrates a significantly improved therapeutic index compared to JH-FK-08, our lead compound to date. NMR binding studies with C32-derivatives are consistent with our hypothesis that C32 modifications disrupt the hydrogen bonding network in the human complex while introducing favorable electrostatic and cation–π interactions with the fungal FKBP12 R86 residue. These findings further reinforce calcineurin inhibition as a promising strategy for antifungal therapy.